Septuagintas betydning for udfoldelsen af nytestamentlig teologi - Müller, Mogens (Dansk Teologisk Tidsskrift, 2016)
The old Greek translation of the sacred books of Judaism, the so-called Septuagint, became the first Bible of the Christian Church. Among other things, this meant that much of the vocabulary and many of the theological concepts of the Jewish sacred texts were already available in a Greek form. On the other hand, this fact also had the consequence that the understanding of the underlying Hebrew text and its eventual interpretation by the translators were taken over by the New Testament authors, beginning with the apostle Paul. The first part of this article summarizes parts of the discussion of the role of the Septuagint as the ‘Bible’ text of the New Testament and its impact on the formation of New Testament theology